Talking Sticks as a Technique to Stimulate the Students' Speaking Performance - St . Hartina (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2020)
Talking sticks is an alternative teaching technique to support students in developing their speaking performance. Holding the talking sticks empower the deep communication between people and allow opportunities to speak up during the classroom. Thus, the present study is to stimulate the students' speaking performance in EFL classroom by utilizing the talking sticks.  It applied classroom action research which was conducted in four stages; planning, action, observation, and reflection. A total of 22 students is the subject of speaking tests, observation, and interviews. The results demonstrated a significant improvement of students' speaking performance which can be seen in the mean score result and the number of students passing the minimal standard score. The mean score gained 9.43 higher than in the pre-test and 77% of students passed the minimal standard score. Both of these criteria indicated that utilizing the talking stick can boost the students' speaking performance